Religious Leadership and Political Triumph: A Case Study of Kiai and Santri Strategies in the 2018 Pamekasan Local Elections - Abd Rohman (CV. Era Digital Nusantara, 2023)
Abstract: This research examines the Kiai Pondok Strategy employed by an Islamic boarding school and its students (known as Santri) in successfully supporting a candidate for the position of Regent and Deputy Regent in the 2018 Regional Election in Pamekasan. Studying this subject is crucial due to the prevailing influence of terms such as